Application of double loop electrochemical potentio-kinetic reactivation for characterizing the intergranular corrosion susceptibility of stainless steels and Ni-based alloys in solar nitrate salts used in CSP systems. (November 2021) - Liu, Qingyang; Qian, Jiong; Barker, Richard; Wang, Chun; Neville, Anne; Pessu, Frederick
Highlights: The DL-EPR was deployed to investigate the DOS in materials in molten salt systems. The tendency for IGC increased after aging in molten salt at CSP system temperatures. DL-EPR studied the synergic effect of molten salt and temperature on IGC tendency. Abstract: In this study, the sensitivity of four corrosion resistant candidate alloys; austenitic stainless steels (AISI 321 and AISI 347) and Ni-based alloys (IN 625 and In 825) to degrade by intergranular corrosion when used with molten salts in conditions of CSP systems were investigated at different temperatures. This was achieved by implementing the Double loop electrochemical potentiokinetic reactivation (DL-EPR) technique to quantitatively measure the degree of sensitisation (DOS) in the selected alloys by aging in air with and without Solar Salts (60 wt% NaNO3 and 40 wt% KNO3 ) at 550–750 °C for 2 h. Electrochemical etching technique was implemented further to verify the results from DL-EPR. The results show that DL-EPR and microstructural evaluation techniques can be used to assess the synergy of temperature and molten salt electrochemical activities on the tendency for intergranular corrosion attack to occur in CPS systems. IN 625 showed the highest intergranular corrosion resistance among the alloys investigated in both air and molten salt; especially at temperatures higher than salt stability temperature. Samples aged in molten salts showed higher DOS than samples aged in air across all temperatures and linked to Cr-consuming corrosion and chemical reactions that drives molten salt – alloy interaction in CSP plants.